REALIZAREA DIMENSIUNILOR EXTERNE ŞI INTERNE ÎN PROCESUL DE INTEGRARE EUROPEANĂ A REPUBLICII MOLDOVA: EVOLUŢIE ŞI ACTUALITATE - Morari, Cristina (CEP USM, 2016)
Integrarea europeană este un proces complex care se realizează prin intermediul dimensiunilor externe şi interne. Dimensiunea externă implică factorul UE şi politica de condiţionalitate a UE. Dimensiunea internă include europenizarea, democratizarea şi modernizarea. În acest articol autorul analizează realizarea dimensiunilor externe şi interne în procesul de integrare europeană a Republicii Moldova.

European integration process is a complex process and is realized through its external and internal dimensions. External dimension implies EU factor and EU conditionality. Internal dimension consists of europeanization, democratization and modernization. In this article the author analyze the realization of external and internal dimensions in the European integration process of the Republic of Moldova.
REALIZATION OF EXTERNAL AND INTERNAL DIMENSIONS IN THE EUROPEAN INTEGRATION PROCESS OF THE REPUBLIC OF MOLD OVA: EVOLUTION AND ACTUALITY
Keywords: integrare europeană; Republica Moldova; UE; Acord de Asociere; European integration; Republic of Moldova; Association Agreemen